2019
DOI: 10.1177/0262489319843645
|View full text |Cite
|
Sign up to set email alerts
|

The effect on the surface activity and the structure of SPI caused by cleavage of disulfide bonds and by subsequent glucose modification

Abstract: The main purpose of this study was to investigate the effects on the molecular structure and the properties of soybean proteins isolate (SPI) after two modifications: (1) peracetic acid oxidative cleavage of its disulfide bonds and (2) the subsequent addition of covalently bonded glucose to the SPI containing the cleaved disulfide bonds. An appropriate amount of peracetic acid will be capable of enhancing the surface properties of SPI significantly; however, excessive oxidation can obtain undesirable results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…β‐sheet was a regular hydrogen bond formed between carbonyl oxygen and the same or adjacent peptide chain and hydrogen through a peptide bond, the increase of β‐sheet content improved the rigidity and compactness of the protein structure 33 . These CD spectroscopy results proved the conformational change of SPI upon MD and MP interaction, the decrease of α‐helix and the increase of β‐sheet enhanced the flexibility of protein, and made the complex structure more stable 34 . Zhao et al .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…β‐sheet was a regular hydrogen bond formed between carbonyl oxygen and the same or adjacent peptide chain and hydrogen through a peptide bond, the increase of β‐sheet content improved the rigidity and compactness of the protein structure 33 . These CD spectroscopy results proved the conformational change of SPI upon MD and MP interaction, the decrease of α‐helix and the increase of β‐sheet enhanced the flexibility of protein, and made the complex structure more stable 34 . Zhao et al .…”
Section: Resultsmentioning
confidence: 69%
“…33 These CD spectroscopy results proved the conformational change of SPI upon MD and MP interaction, the decrease of ⊍-helix and the increase of ⊎-sheet enhanced the flexibility of protein, and made the complex structure more stable. 34 Zhao et al reported similar results that a decrease in ⊍-helix and an increase in ⊎-sheet content were observed for SPI with betalain. 16 MP, SPI and MD interacted to produce complexes, in which the structure of MP-SPI-MD had more hydrogen bonds, thereby improving the stability of MP and better resistance to photodegradation.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 56%
“…The molecular weights of β-conglycinin and glycinin are ∼150-200 and 300-380 kDa, respectively, 43 compared to ∼18 kDa for β-lactoglobulin and ∼14 kDa for α-lactalbumin. SPI also has more disulfide bonds (β-conglycinin and glycinin have 2 and 20 disulfide bonds, respectively 44 ) than WPI (β-lactoglobulin and α-lactalbumin have 2 and 4 disulfide bonds, respectively 16 ), conferring a stiffer structure. A more rigid structure that was obtained with the SPI may have caused more wrinkles at the surface of the powder particles, as seen in SEM images.…”
Section: Particle Morphologymentioning
confidence: 99%